Percutaneous transforaminal endoscopic decompression with removal of the posterosuperior region underneath the slipping vertebral body for lumbar spinal stenosis with degenerative lumbar spondylolisthesis: a retrospective study - Rongbo Yu; Xiaokang Cheng; Bin Chen (BMC Musculoskeletal Disorders, 2024)
Abstract Background Percutaneous transforaminal endoscopic decompression (PTED) is an ideal minimally invasive decompression technique for the treatment of lumbar spinal stenosis (LSS) with degenerative lumbar spondylolisthesis (DLS). The posterosuperior region underneath the slipping vertebral body (PRSVB) formed by DLS is an important factor exacerbating LSS in patients. Therefore, the necessity of removing the PRSVB during ventral decompression remains to be discussed. This study aimed to describe the procedure of PTED combined with the removal of the PRSVB and to evaluate the clinical outcomes. Methods LSS with DLS was diagnosed in 44 consecutive patients at our institution from January 2019 to July 2021, and they underwent PTED combined with the removal of the PRSVB. All patients were followed up for at least 12 months. The clinical outcomes were evaluated using the visual analog scale (VAS), Oswestry Disability Index (ODI), and modified MacNab criteria. Results The mean age of the patients was 69.5 ± 7.1 years. The mean preoperative ODI score, VAS score of the low back, and VAS score of the leg were 68.3 ± 10.8, 5.8 ± 1.0, and 7.7 ± 1.1, respectively, which improved to 18.8 ± 5.0, 1.4 ± 0.8, and 1.6 ± 0.7, respectively, at 12 months postoperatively. The proportion of patients presenting “good” and “excellent” ratings according to the modified MacNab criteria was 93.2%. The percent slippage in spondylolisthesis preoperatively (16.0% ± 3.3%) and at the end of follow-up (15.8% ± 3.3%) did not differ significantly (p>0.05). One patient had a dural tear, and one patient had postoperative dysesthesia. Conclusions Increasing the removal of PRSVB during the PTED process may be a beneficial surgical procedure for alleviating clinical symptoms in patients with LSS and DLS. However, long-term follow-up is needed to study clinical effects.